Characterizing Old Greek Deuteronomy as an Ancient Translation - Maurais, Jean, (Supplements to the Journal for the Study of Judaism ;, 2022)
Much can be learned about a translation's linguistic and cultural context by studying it as a text, a literary artifact of the culture that produced it. However, its nature as a translation warrants a careful approach, one that pays attention to the process by which its various features came about. In Characterizing Old Greek Deuteronomy as an Ancient Translation, Jean Maurais develops a framework derived from Descriptive Translation Studies to bring both these aspects in conversation. He then outlines how the Deuteronomy translator went about his task and provides a characterization of the work as a literary product.